Biological Activity of the Coordinating Compound of Qinazolin-4-One with Nickel-(II) Nitrate Hexahydrate (Texas Journal of Agriculture and Biological Sciences, 2023)
We performed the following processes in the study of the biochemical effects of the coordination compound formed with nickel (II)-nitrate and quinazolin-4-one on the "amber" variety of the Phaseolus aureus plant.